VD_FINDINFO Décision / 2020 / 404 vom 19. Mai 2020 - VD Tribunal cantonal (2020)
JUGE UNIQUE, NON-LIEU, ADMISSION DE LA DEMANDE | 132 al. 1 let. b CPP (CH), 319 CPP (CH), 423 al. 1 CPP (CH), 426 al. 2 CPP (CH), 429 al. 1 let. a CPP (CH), 430 al. 1 let. a CPP (CH)